Electrically tunable singular phase and Goos–Hänchen shifts in phase-change-material-based thin-film coatings as optical absorbers - Sreekanth, Kandammathe Valiyaveedu (2021)
The change of the phase of light under the evolution of a nanomaterial with time is a promising new research direction. A phenomenon directly related to the sudden phase change of light is the Goos-Hänchen (G-H) shift, which describes the lateral beam displacement of the reflected light from the interface of two media when the angles of incidence are close to the total internal reflection angle or Brewster angle. Here, an innovative design of lithography-free nanophotonic cavities to realize electrically tunable G-H shifts at the singular phase of light in the visible wavelengths is reported. Reversible electrical tuning of phase and G-H shifts is experimentally demonstrated using a microheater integrated optical cavity consisting of a dielectric film on an absorbing substrate through a Joule heating mechanism. In particular, an enhanced G-H shift of 110 times of the operating wavelength at the Brewster angle of the thin-film cavity is reported. More importantly, electrically tunable G-H shifts are demonstrated by exploiting the significant tunable phase change that occurs at the Brewster angles, due to the small temperature-induced refractive index changes of the dielectric film. Realizing efficient electrically tunable G-H shifts with miniaturized heaters will extend the research scope of the G-H shift phenomenon and its applications.